Evaluation of MRI Features and Neurodevelopmental Outcomes for Prenatally Diagnosed Periventricular Pseudocysts - Sun, Cong; Zhang, Xinjuan; Chen, Xin; Wei, Xinhong; Chen, Yufan; Yang, Aocai; Zhu, Jinxia; Wang, Guangbin (Frontiers in Pediatrics, 2021)
Objectives This study aims to evaluate the morphological features and neurodevelopmental outcomes of individuals prenatally diagnosed with periventricular pseudocysts (PVPC). Methods Pregnant women with a fetus prenatally diagnosed with PVPC by MRI were enrolled in this retrospective study. The fetuses with PVPC were divided into group 1 (isolated PVPC) and group 2 (PVPC with additional findings). The surviving subjects underwent brain MRI examinations and Gesell Developmental Scale (GDS) tests after birth. The independent sample t-tests were used to compare the differences of the developmental quotient (DQ) between group 1 and group 2. We also analyzed the correlations among the DQ, the location (unilateral/bilateral), the size (diameter), and the number (single /multiple) of the PVPC in group 1 using the Lasso regression. Results 131 subjects (group 1: 78 subjects, group 2: 53 subjects) underwent MRI examinations after birth, and 97 subjects (group 1: 59 subjects, group 2: 38 subjects) underwent the GDS test. According to the follow-up findings, the sizes of the cysts usually became smaller or disappeared after birth. The average DQ in group 2 was lower than those in group 1 (all with p < 0.001). In group 1, the location (unilateral/bilateral), size (diameter), and number (single /multiple) of the PVPC did not affect the DQ. Conclusions The PVPC becomes smaller or disappears after birth. Isolated PVPCs usually have a normal presentation after birth regardless of the location, number and size. With PVPCs with additional findings, the neurodevelopmental outcomes were inferior to that in isolated PVPCs.